Association of candidate genes for fatty acid content in soybean by temperature-switch PCR (TSP) genotyping - Bueno, Rafael Delmond; God, Pedro Ivo Vieira Good; Prata, Isadora Oliveira; Pereira, Pedro Henrique Scarpelli; Teixeira, Arlindo Inês; Piovesan, Newton Deniz; Barros, Everaldo Gonçalves de (Crop Breeding and Applied Biotechnology, 2018)
The development of molecular markers is essential for improvement of soybean cultivars with modified fatty acid content. The objective of this study was to identify and validate SNP markers in candidate genes for fatty acid content in soybean. Six candidate genes (ARAF, PDAT, ABI3, FAD2-1b, FAD3B, and FAD3C) were selected. Alignment of gene sequences identified 25 SNPs and 3 INDELs. TSP primers were used to identify SNP alleles. 259 recombinant inbred lines (RILs) (FA22 / CD219) and 185 F2 progenies (A29 / Tucunaré) were tested for association of SNPs. An SNP for FAD3B was associated with variation in content of linoleic acid (R2 = 5.84%) and linolenic acid (R2 = 6.79%). In FAD3C, an SNP was associated with linoleic and linolenic acids (R2 of 9.21% and 18.51%, respectively). The ABI3 gene was associated with palmitic acid, with R2 = 5.41%. The SNP markers identified will be used in assisted selection for improvement of fatty acid content.
Keywords: Low linolenic acid; MAS- marker- assisted selection; SNP- single nucleotide polymorphism